Dielectric and mechanical properties of mullite/modified batio3composites - Narumon Lertcumfu (2018)
© 2016 Trans Tech Publications, Switzerland. Composites between mullite and modified BT were prepared by a conventional technique. The samples were calcined at 1300 °C for 2 h. The composites were sintered at 1250 °C for 2 h. The dielectric and mechanical properties samples were investigated. The mechanical properties were found to improve after sintering at a suitable temperature. Addition of the BT produced an improvement in dielectric constant due to the BT has high piezoelectric properties. A higher dielectric constant for a sample contained higher amount of the BT was related with a higher polarization in the samples.